2022
DOI: 10.3390/pharmaceutics14112529
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Assessment of Mannitol Accumulation Following Osmotic Blood–Brain Barrier Opening Using Chemical Exchange Saturation Transfer Magnetic Resonance Imaging

Abstract: Purpose: Mannitol is a hyperosmolar agent for reducing intracranial pressure and inducing osmotic blood–brain barrier opening (OBBBO). There is a great clinical need for a non-invasive method to optimize the safety of mannitol dosing. The aim of this study was to develop a label-free Chemical Exchange Saturation Transfer (CEST)-based MRI approach for detecting intracranial accumulation of mannitol following OBBBO. Methods: In vitro MRI was conducted to measure the CEST properties of D-mannitol of different con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 89 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…CEST is based on application of radiofrequency pluses to a selected pool of molecules at a frequency that causes loss of magnetization (saturation) of its protons to the protons of the surrounding and larger water pool ( Kogan et al, 2013 ). This exchange of protons or ‘chemicals’ is the CEST signal that is further enhanced using exogenous agents, of which D-glucose is commonly used in indirect imaging of BBB ( Elschot et al, 2021 ; Harris et al, 2023 ) - although other agents such as Salicylic Acid Analogues ( Song et al, 2016 ) and Mannitol have been demonstrated in intra-arterial administration in rodent ischemic stroke models ( Song et al, 2016 ; Liu et al, 2022 ). Challenges with obtaining the arterial input function to model glucose concentration in the parenchyma, its transport and utilization, the relatively long imaging time from application of multiple long TR saturation pulses, and importantly the lack of validation of CEST agents for BBB, present limitations its routine clinical use ( Kogan et al, 2013 ; Harris et al, 2023 ).…”
Section: Devicementioning
confidence: 99%
“…CEST is based on application of radiofrequency pluses to a selected pool of molecules at a frequency that causes loss of magnetization (saturation) of its protons to the protons of the surrounding and larger water pool ( Kogan et al, 2013 ). This exchange of protons or ‘chemicals’ is the CEST signal that is further enhanced using exogenous agents, of which D-glucose is commonly used in indirect imaging of BBB ( Elschot et al, 2021 ; Harris et al, 2023 ) - although other agents such as Salicylic Acid Analogues ( Song et al, 2016 ) and Mannitol have been demonstrated in intra-arterial administration in rodent ischemic stroke models ( Song et al, 2016 ; Liu et al, 2022 ). Challenges with obtaining the arterial input function to model glucose concentration in the parenchyma, its transport and utilization, the relatively long imaging time from application of multiple long TR saturation pulses, and importantly the lack of validation of CEST agents for BBB, present limitations its routine clinical use ( Kogan et al, 2013 ; Harris et al, 2023 ).…”
Section: Devicementioning
confidence: 99%
“…To tackle the invasive nature of the hyperosmolar process, researchers have devised an MRI technique that relies on unenhanced chemical exchange saturation transfer to identify the buildup of mannitol in the intracranial region after the opening of the BBB. This technique holds promise as a prompt imaging tool for optimizing the administration of mannitol-based BBB opening, thereby enhancing its safety and effectiveness [116]. Moreover, implementing hyperosmolar BBB opening techniques in murine models using MRI guidance can effectively mitigate the limitations of inconsistent reproducibility and heterogeneous experimental results commonly observed with the intra-arterial administration of hyperosmolar mannitol [117].…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…Detailed descriptions of CEST MRI can be found in several excellent review papers. As NMR-rooted techniques, CEST MRI and MRS share many common physics and chemistry principles and practices. They are also complementary and can be used in combination, as it was demonstrated by Liu et al in their work on using CEST MRI and MRS to investigate mannitol accumulation following the osmotic blood–brain barrier (BBB), in which mannitol in the brain can be directly measured by both CEST and MRS signals . Their results suggested that MRS had low spatial resolution but high specificity, whereas those by CEST MRI had high spatial resolution and high sensitivity.…”
Section: Cest Based Molecular Imagingmentioning
confidence: 99%
“…They are also complementary and can be used in combination, as it was demonstrated by Liu et al in their work on using CEST MRI and MRS to investigate mannitol accumulation following the osmotic blood–brain barrier (BBB), in which mannitol in the brain can be directly measured by both CEST and MRS signals. 93 Their results suggested that MRS had low spatial resolution but high specificity, whereas those by CEST MRI had high spatial resolution and high sensitivity. Quantifying CEST images is much more complicated than MRS as signals are from exchangeable protons with an exchange rate that is dependent on various chemical and biochemical conditions.…”
Section: Cest Based Molecular Imagingmentioning
confidence: 99%